A Novel Microtubule-Tau Association Enhancer and Neuroprotective Drug Candidate: Ac-SKIP - Ivashko-Pachima, Yanina; Gozes, Illana (Frontiers in Cellular Neuroscience, 2019)
Activity-dependent neuroprotective protein (ADNP) has been initially discovered through its eight amino acid sequence NAPVSIPQ, which shares SIP motif with SALLRSIPA – a peptide derived from activity-dependent neurotrophic factor (ADNF). Mechanistically, both NAPVSIPQ and SALLRSIPA contain a SIP motif that is identified as a variation of SxIP domain, providing direct interaction with microtubule end-binding proteins (EBs). The peptide SKIP was shown before to provide neuroprotection in vitro and protect against Adnp-related axonal transport deficits in vivo. Here we show, for the first time that SKIP enhanced microtubule dynamics, and prevented Tau-microtubule dissociation and microtubule disassembly induced by the Alzheimer’s related zinc intoxication. Furthermore, we introduced, CH3CO-SKIP-NH2 (Ac-SKIP), providing efficacious neuroprotection. Since microtubule - Tau organization and dynamics is central in axonal microtubule cytoskeleton and transport, tightly related to aging processes and Alzheimer’s disease, our current study provides a compelling molecular explanation to the in vivo activity of SKIP, placing SKIP motif as a central focus for MT-based neuroprotection in tauopathies with axonal transport implications.